Analisis Efektivitas Program Pendampingan Rumah BUMN Kabanjahe dalam Meningkatkan Kapasitas Usaha Mikro di Kabanjahe - Oby Heber Eginta Tarigan; Frans Antoni Sihite; Ingan Ukur Br Sitepu; Menanti Br Sembiring (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving the regional economy, including in Kabanjahe District, Karo Regency. However, micro-enterprises still face various challenges, such as limited managerial skills, low product innovation, and minimal use of digital marketing. To empower MSMEs, the government, through the Ministry of State-Owned Enterprises, has launched the Rumah BUMN program, which focuses on business training and mentoring. This study aims to analyze the effectiveness of the Rumah BUMN Kabanjahe mentoring program in increasing the capacity of micro-enterprises and to identify supporting and inhibiting factors in its implementation.This study used a qualitative approach with descriptive methods. Data were obtained through in-depth interviews, observations, and documentation with the managers of Rumah BUMN Kabanjahe and the micro-entrepreneurs under their guidance. then analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was tested using triangulation. The results indicate that the Rumah BUMN Kabanjahe mentoring program is quite effective in increasing the capacity of micro-entrepreneurs, as indicated by improvements in managerial skills, product innovation, and the use of digital marketing. However, obstacles remain, including limited supporting facilities, differing levels of business readiness, and suboptimal mentoring sustainability. Therefore, strengthening the mentoring system and ongoing collaboration is necessary for the program to deliver maximum impact.